Pembunuhan Tradisi Peasen - Musa, Farid Th. (Jurnal Pelangi Ilmu, 2008)
Processing of natural resources especially is agricultural sector entangles two different groups oriented to agro product. The difference surrounded by importance to production having usage value and exchange rate in agricultural land processing. This Exchange Rate and usage value differentiates modern traditional agricultural system and agriculture system. Traditional agricultural system is done to fulfill requirement of food, what done by farmer based on knowledge they to correspond to nature ferocity. To fulfill requirement of the food, more opting farmer applies resource which there is around their life. For traditional farmer embracing principle \'\'prioritizes safing\", agriculture product is addressed to fulfill requirement of food for family While for modern agriculture system, done based on innovation of tending to agriculture orienteds at produce of get advantage. It is peripatetic giant companys is area food to create agriculture system using seed hibrida and chemical material namely defoliant and roundup to increase product agriculture. Usage of this hibrida seed kills efficiency of farmer as seed producer, and usage of defoliant and roundup which is dangerous as an action of murder to efficiency of farmer and itself farmer.